The Impact of Uncertainty and Macroeconomic on Income Inequality in Indonesia - A, Lathif Arafat; Meilisa, M; Meta, Williya (Universitas 17 Agustus 1945 Surabaya, 2025)
One of the causes of income inequality is uncertainty shocks. These shocks impact the broader macroeconomy, which, in turn, aff ects inequality. This study examines income inequality in Indonesia, aff ected by global and macroeconomic uncertainties, by using the ARDL and ECM co-integration bound tests to analyze both long-term and short-term relationships over the period from 1991 to 2021. The results of the study indicate a long-term eff ect of global uncertainty on income inequality in Indonesia. Additionally, both long-term and short-term variables, such as unemployment and income, also infl uence income inequality in Indonesia.